USING MULTI-TEMPORAL REMOTE SENSING DATA TO QUANTIFY FOREST COVER CHANGE IN DIEN BIEN DONG DISTRICT, DIEN BIEN PROVINCE DURING 1991 - 2017 - Hong Son, Lo; Hai Hoa, Nguyen; Gabriela Flores Montenegro, Diana; Thi Thu Hien, Nguyen; Hoang Vuong, Dang; Thi Bich Hao, Nguyen (Journal of Forestry Science and Technology, 2018)
Quantifying temporal changes of land use and land cover (LULC), in particular forest covers from satellite images at the various scales has been conducted in Vietnam for several years. However, a few studies have carried out to investigate LULC in Dien Bien Dong district. Hence, using multi-temporal remote sensing data to quantify LULC changes was conducted in Dien Bien Dong district, Dien Bien province during 1991 - 2017. In this study, Landsat data, including Landsat 5 (TM) in 1991, 1999 and 2009, and Landsat 8 (OLI) for 2017 with spatial resolution of 30 m was used to quantify the spatial changes of forest cover exents and then defined the drivers of changes. NDVI (Normalized Difference Vegetation Index) in combination with unsupervised classification was used. As a result showed that there was a change in forest cover extents from 1991 to 2017. Accuracy assessments of classified forest cover maps indicated that there was relatively high accurate with over 85.0%. In particular, forest cover extents declined in the period of 1991 - 2017 from 49,351.7 ha to 37,414.6 ha (decreased by 11,937.1 ha). Forest cover extents decreased by 1,683.7 ha, 9,268.7 ha and 984.6 ha in the period of 1991 - 1999, 1999 - 2009 and 2009 - 2017, respectively. Main drivers of forest cover extents were due to human forces, such as slash and burning, shifting cultivation.